RESOURCE AND EXPLOITATION OF JUVENILE PENAEID PRAWNS FROM MANAKKUDY ESTUARY - Suseelan, C (Indian Journal of Fisheries, 2011)
The Manakkudy Estuary situated about 8 kilometres north of Cape Comorinin Tamil Nadu is an important source of juvenile penaeid prawns which are usedas bait in hook-and-line fisheries and seed for culture, along the coasts of KanyakumariDistrict. It is estimated that 4 tonnes of juvenile prawns are exploited onan average every year from this environment, with peak catches in February andMarch. The fishery is constituted by Penaeus irulicus, P. monodon, Metapenaeusdobsord and M. monoceros. Of these, P. indicus is the most dominant speciesforming 90% of the total prawn catch. By following the progression of modes in(he size-frequency distribution it is estimated that males of this species grow atthe rate of 24.3 mm|month and females, 26.2 mm|month. The maximum growthrates are recorded mostly